(untitled) (ELEKTRIKA- Journal of Electrical Engineering, 2025)
Silicon-on insulator (SOI) photonic crystal (PhC) slabs are anticipated to play a critical role in advancing photonic devices for telecommunication and optical circuits. However, achieving high quality(Q)-factor and low mode volume remains a significant challenge in designing these structures. In this study, we propose a two-dimensional (2D) PhC structure by modulating the waveguide width and three different nanocavities formations created by shifting the selected air holes at the center of the structure. By using 3D finite-difference time-domain (FDTD) simulations, transmittance spectrum properties we analyzed. We have achieved the highest values of 2.07×106 at 1.5447 μm for nanocavity shifted distance of 3 nm, 6 nm and 6 nm without cladding layer added. Furthermore, the challenge lies in minimizing the vertical scattering loss when different cladding materials are introduced. Through this simulation, we found that cladding layers impact the transmittance spectrum. The highest Q-factor is 1.41×106 with mode volume of 0.826 if clad materials with silica (SiO2). These findings demonstrate significant potential for integrating high-Q PhC structure into advanced optical devices, enhancing performance in telecommunication and photonic circuits.